Kajian Pola dan Makna Kontekstual Perkataan Basar dalam Surah al-Isra’: A Study of the Pattern and Contextual Meaning of Word Basar in Surah al-Isra’ - Mohd, Robiatul Adawiyah; Baharuddin, Nur Farhana; Hajib, Zainal Abidin; Mohd Ghazali, Norzulaili; Ahmad, Hishomudin (Maʿālim al-Qurʾān wa al-Sunnah, 2018)
Quran is a scripture that was revealed in the last 15 centuries. Each letter, word, verse, and sura contains a perfect and beautiful pattern. Each pattern in the Quran has significant meaning to be studied. Generally, the study of the Quranic pattern has been carried out. However, there is no specific study of the word-based pattern in the Quran especially the word basar. Furthermore, existing Quranic translations have not taken into account the contextual meaning of a word in their translation. Hence, this study aims to examine the basar word pattern in surah al-Isra’, analyze the meaning of the word basar and classify it based on the thematic approach. This paper is a conceptual work paper using qualitative methods and content analysis methods based on the thematic approach. The findings of the study show that there are 8 repetitions of the word basar in surah al-Isra’. The finding of this study also found that each word basar has different meanings based on the derivation and the contextual meaning of each verse. Such special understanding should be examined more broadly on the words contained in the Quran, especially the existing Quranic translations do not take this approach in their translation.